Bipolar disorder comorbidity in patients with obsessive-compulsive disorder: Prevalence and predictors - Domingues-Castro, Mariana S. [UNESP]; Torresan, Ricardo C. [UNESP]; Shavitt, Roseli G.; Fontenelle, Leonardo F.; Ferrão, Ygor A.; Rosário, Maria C.; Torres, Albina R. [UNESP] (Elsevier, 2019)
Background: Patients with obsessive-compulsive disorder (OCD) often present with comorbidities, mainly anxiety and affective disorders, which may influence OCD course, help-seeking and treatment response. Some authors have studied bipolar disorder (BD) comorbidity in patients with OCD, but usually in small samples. The objective was to estimate the lifetime prevalence of BD in a large clinical sample of OCD patients, and to compare demographic and clinical features of patients with and without BD comorbidity. Method: This cross-sectional study with 955 adult OCD patients from the Brazilian Research Consortium on Obsessive-Compulsive Spectrum Disorders (C-TOC) used several assessment instruments, including the Yale-Brown Obsessive-Compulsive Scale, the Dimensional Yale-Brown Obsessive-Compulsive Scale, the Beck Depression and Anxiety Inventories, and the Structured Clinical Interview for DSM-IV Axis I Disorders. Descriptive and bivariate analyses were followed by logistic regression. Results: The lifetime prevalence of BD was 7.75% (N = 74). The variables that were independently associated with BD comorbidity were: panic disorder with agoraphobia, impulse control disorders, and suicide attempts. Limitations: The cross-sectional design does not permit causal inferences; the external validity may be limited, as the participants were from tertiary services. Despite the large sample size, some analyses may have been underpowered due to the relatively low prevalence of the outcome and of some explanatory variables. Conclusions: Patients with OCD comorbid with BD have some clinical features indicative of greater severity, including higher suicide risk, and require a careful therapeutic approach for the appropriate treatment of both disorders.
Keywords: Bipolar disorder; Comorbidity; Obsessive-compulsive disorder; Phenomenology